Pengembangan Media Explosion box Sebagai Pengenalan Sejarah Bangsa Indonesia Pada Siswa Sekolah Dasar - Sufie Aulya Rahmadhany; Ratih Asmarani (IJPSE : Indonesian Journal of Primary Science Education, 2023)
The problems studied are how to develop explosion box media, the quality of explosion box media and how to apply explosion box media. With the aim of knowing the process of developing explosion box media, the quality of explosion box media and the application of explosion box media at SDN Sugihwaras 1 Jombang. This research uses development research (R&D) methods. With a 4-D model developed by S. Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel. The subjects of this study were fourth grade students at SDN Sugihwaras 1 Jombang. This research was conducted from February to June 2022. The methods used were observation, interviews, documentation and questionnaires. Data analysis was obtained using a Likert scale. Based on the results of the analysis that has been done, the explosion box learning media has an average value of 92.21%. According to Purwanto, the Five Scale Rating category is divided into 5, namely very decent, decent, fairly decent, less feasible and not feasible. 3). The application of explosion box media as an effort to introduce the history of the Indonesian nation to fourth grade students at SDN Sugihwaras 1 Jombang shows that the response of students to the learning media developed by researchers is good and can be accepted by students during the learning process. In addition to getting a very good response from students, the researchers also got a good response from educators with an average percentage of 82.6%, which means that the explosion box learning media is indeed suitable for use by students.